Changing Population, Landuse and Environment in the Nepal Himalayas - Chapagain, Prem Sagar (Journal of Hydrology and Meteorology, 2016)
Mountain environment is a matter of global concern. In the case of Nepal, population size has been ever increasing with rapid growth rate until 2001. With increasing population size and growth rate, major changes appeared in land use pattern, i.e. increasing agricultural land and decreasing forest coverage. This has alarmed the situation especially during 1980s as it was linked with highland deforestation for agricultural land to fulfill the increasing food demand that resulted lowland sedimentation and flooding. However, population growth rate between 2001-2011 has drastically decreased compared to the past decade. At the same time, literacy and environmental awareness increased, alternative means of income and employment opportunities have increased and poverty has decreased. These changes including the policy of forest management have contributed positively in forest coverage. It has also succeeded to break the previous environmental orthodoxy, population growth- food demand-deforestation/degradation nexus, in the Nepal Himalayas. Journal of Hydrology and Meteorology, Vol. 8(1) 2012, p.66-71